Risk and timing of biochemical recurrence in pT3aN0/Nx prostate cancer with positive surgical margin - A multicenter study - Karl, Alexander; Buchner, Alexander; Tympner, Christiane; Kirchner, Thomas; Ganswindt, Ute; Belka, Claus; Ganzer, Roman; Wieland, Wolf; Eder, Fabian; Hofstaedter, Ferdinand; Schilling, David; Sievert, Karl-Dietrich; et al. (Radiotherapy and Oncology, 2015)
Positive surgical margins (PSM) after radical prostatectomy have been shown to be associated with impaired outcome. In pT3pN0 patients with PSM either immediate radiotherapy or clinical and biological monitoring followed by salvage radiotherapy is recommended by the latest guidelines of the European Association of Urology.A retrospective, multicenter study of eight urological centers was conducted on 536 prostatectomy patients with pT3aN0/NxR1 tumors and no neoadjuvant/adjuvant therapy. A pathological re-review of all prostate specimens was performed. Association of clinical and pathological features with biochemical recurrence (BCR) was analyzed using univariate and multivariate analysis.With 48months median follow-up, BCR occurred in 39.7%. Preoperative PSA value, performance of pelvic lymph node dissection and Gleason score were significantly associated with BCR. In multivariate analysis, Gleason score was the only independent prognostic factor (p<0.001) for BCR. Five-year BCR-free survival rates were 74%, 70%, 38%, and 51% with Gleason score 6, 3+4=7a, 4+3=7b, and 8-10, respectively.In pT3aN0/NxR1 patients with no adjuvant/neoadjuvant treatment, Gleason Score permits independent prediction of the risk for BCR. These findings could help to estimate and discuss the individual risk for BCR with our patients on an individual basis.
EVALuna2:6761